Nudging fast and slow: Experimental evidence from food choices under time pressure - Paul Lohmann; Elisabeth Gsottbauer; Christina Gravert; Lucia A. Reisch (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
This paper explores the relationship between decision-making speed and the effectiveness of two nudges - carbon footprint labelling and menu repositioning - aimed at encouraging climate-friendly food choices. Building on Kahneman's dual-process theory of decision-making, we examine whether these interventions are more effective in fast, intuitive (System 1) contexts compared to reflective, deliberate (System 2) ones. Using an incentivized online randomized controlled trial with a quasirepresentative sample of British consumers (N=3,052) ordering meals through an experimental food-delivery platform, we introduced a time-pressure mechanism to capture both fast and slow decision-making processes. Our findings suggest that menu repositioning is an effective tool for promoting climate-friendly choices when decisions are made quickly, though the effect fades with extended deliberation. Carbon labels, in contrast, showed minimal impact overall but reduced emissions among highly educated, climate-conscious individuals under time pressure. The results imply that choice architects should apply both interventions in contexts where consumers make rapid decisions, such as digital platforms, to help mitigate climate externalities.
Keywords: C90; D04; I18; D90; Q18; Q50; 330; carbon-footprint labelling; choice architecture; food-delivery apps; low-carbon diets; dual-process models; system 1